2016
DOI: 10.1007/s12010-016-2191-8
|View full text |Cite
|
Sign up to set email alerts
|

High Cell Density Process for Constitutive Production of a Recombinant Phytase in Thermotolerant Methylotrophic Yeast Ogataea thermomethanolica Using Table Sugar as Carbon Source

Abstract: The yeast Ogataea thermomethanolica has recently emerged as a potential host for heterologous protein expression at elevated temperature. To evaluate the feasibility of O. thermomethanolica as heterologous host in large-scale fermentation, constitutive production of fungal phytase was investigated in fed-batch fermentation. The effect of different temperatures, substrate feeding strategies, and carbon sources on phytase production was investigated. It was found that O. thermomethanolica can grow in the tempera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…This yeast can utilize methanol or sucrose to drive the inducible expression of recombinant proteins [ 4 , 5 ]. In addition, it can be cultured to high-cell density on fed-batch fermentation using low-cost substrates, which is advantageous for industrial applications [ 6 , 7 ]. Like other yeasts, efficient secretion is a major bottleneck for heterologous protein production, in which heterologous proteins are often poorly secreted, leading to intracellular accumulation, which triggers endoplasmic reticulum (ER) stress [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…This yeast can utilize methanol or sucrose to drive the inducible expression of recombinant proteins [ 4 , 5 ]. In addition, it can be cultured to high-cell density on fed-batch fermentation using low-cost substrates, which is advantageous for industrial applications [ 6 , 7 ]. Like other yeasts, efficient secretion is a major bottleneck for heterologous protein production, in which heterologous proteins are often poorly secreted, leading to intracellular accumulation, which triggers endoplasmic reticulum (ER) stress [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies of the suggested strain O. thermomethanolica BCC16875 continued during next following years. Pro moters typical for this train were studied (Harnpicharnchai et al, 2014;Promdonkoy et al, 2014), as well as methods of highdensity cultivation for expression of recombinant proteins (Charoenrat et al, 2016). Besides, work on optimization of strain's metabolism for increase of target products' output was started.…”
Section: Phylogenic Analysismentioning
confidence: 99%
“…Based on its indigenous methanol-inducible promoter and secretion signal, it has been developed as a non-conventional host for production of industrial enzymes [6,7]. The OT system has been tested for large-scale industrial enzyme production using highcell density fermentation [8,9]. Nevertheless, whether the OT system can be utilized for production of high-valued recombinant proteins of non-fungal origins remains to be demonstrated.…”
Section: Introductionmentioning
confidence: 99%